Pyogenic granuloma: Clinicopathological and treatment scenario - Ahmed Salah Al-Noaman (Wolters Kluwer Medknow Publications, 2020)
Background: Oral pyogenic granuloma is a soft-tissue lesion of the oral mucosa. This lesion has a tendency to reoccur after surgical excision. Materials and Methods: A total of 28 patients underwent surgical excision of pyogenic granuloma in the period from September 2014 to May 2016. Two surgical techniques were used to remove pyogenic granuloma: simple excision with root planing and modified excision with deep curettage. Results: Females (54%) were slightly more predominant than males (46%). The upper and lower jaws were almost equally affected by the lesion with more predilection toward the posterior region. The size of the lesion ranged from 0.5 to 3 cm in diameter with slow-growing rate. Rural residents were more affected (57%) than urban people. The lesion appears clinically as a small red mass with sessile base, and these clinical features were similar in pregnant and nonpregnant women. The recurrence rate was 14.8% and seen only in patients treated by simple excision. Histopathological feature was consistent with inflammatory hyperplastic lesion, and there was no radiographic evidence of bone resorption associated with the lesion. Conclusion: Modified excision with deep curettage prevents the recurrence of the lesion after 1-year follow-up.